Effects of C/N ratio on the performance of a hybrid sponge-assisted aerobic moving bed-anaerobic granular membrane bioreactor for municipal wastewater treatment. (January 2018) - Chen, C.; Guo, W.S.; Ngo, H.H.; Chang, S.W.; Nguyen, D.D.; Zhang, J.; Liang, S.; Guo, J.B.; Zhang, X.B.
Graphical abstract: Highlights: Effects of C/N ratio on SAAMB-AnGMBR performance were investigated. Lower C/N ratios negatively affected nutrient removal and granular properties. The SAAMB-AnGMBR exhibited lower fouling propensity at higher C/N ratios. EPS was the influencing factor to membrane fouling at varying C/N ratios. The SAAMB-AnGMBR performance could recover after increasing C/N ratio. Abstract: This study aimed to evaluate the impact of C/N ratio on the performance of a hybrid sponge-assisted aerobic moving bed-anaerobic granular membrane bioreactor (SAAMB-AnGMBR) in municipal wastewater treatment. The results showed that organic removal efficiencies were above 94% at all C/N conditions. Nutrient removal was over 91% at C/N ratio of 100/5 but was negatively affected when decreasing C/N ratio to 100/10. At lower C/N ratio (100/10), more noticeable membrane fouling was caused by aggravated cake formation and pore clogging, and accumulation of extracellular polymeric substances (EPS) in the mixed liquor and sludge cake as a result of deteriorated granular quality. Foulant analysis suggested significant difference existed in the foulant organic compositions under different C/N ratios, and humic substances were dominant when the fastest fouling rate was observed. The performance of the hybrid system was found to recover when gradually increasing C/N ratio from 100/10 to 100/5.